Reconciliation of Philosophical Perspectives to Address Autoethnographic Methodological Concerns - Sibbald, Timothy; Handford, Victoria; Kornelsen, Lloyd (Alberta Journal of Educational Research, 2020)
An instance of editorial work was found to address methodological issues at the juncture of autoethnography and narrative inquiry. The particular case is reported because it addresses the conceptual basis of known methodological issues. The case involved interactions between a chapter author and editors of a book as well as between the editors. Although the chapter was autoethnographic as initially submitted, through the use of research-oriented open-ended questioning, the editors engaged with the author causing the author to gain a deeper insight and richer narrative regarding his own experience. The result bridges the gap between autoethnography and narrative inquiry. Interactions between the editors were directed at providing constructive support while leaving ownership of the narrative with the author. The process has features overlapping and distinct from duoethnography. An empirical explanation is proposed through the reconciliation of philosophical stances of the author and editors. Key words: Autoethnography, narrative inquiry, emergent design, duoethnography, editorial methodology Un exemple de travail éditorial a permis d’aborder des questions méthodologiques à la jonction de l’autoethnographie et de l’enquête narrative. Le cas particulier à l’étude porte sur la base conceptuelle de questions méthodologiques connues. Le cas implique des interactions entre l’auteur d’un chapitre et les éditeurs d’un livre, ainsi que des interactions entre les éditeurs. Bien que le chapitre ait été autoethnographique lors de la soumission initiale, l’emploi par les éditeurs de questions ouvertes axées sur la recherche et communiquées à l’auteur lui a permis d’arriver à des connaissances approfondies et à un récit enrichi relativement à ses propres expériences. Les résultats jettent un pont entre l’autoethnographie et l’enquête narrative. Les interactions entre les éditeurs visaient à apporter un appui constructif tout en permettant à l’auteur de conserver son récit. Certaines caractéristiques du processus chevauchent la duoethnographie; d’autres s’en distinguent. Nous proposons une explication empirique née de la réconciliation des positions philosophiques de l’auteur et des éditeurs. Mots clés: autoethnographie, enquête narrative, modèle émergent, duoethnographie, méthodologie éditoriale